Applications of Brain Organoids for Infectious Diseases. Issue 3 (15th February 2022) - Fan, Wenqiang; Christian, Kimberly M.; Song, Hongjun; Ming, Guo-li
Graphical abstract: Highlights: Current methodologies on different types of brain organoids. Applications of brain organoids in the research of neurotropic viral infection. Limitations of current brain organoid methodologies and future improvement. Abstract: Brain organoids are self-organized three-dimensional aggregates generated from pluripotent stem cells. They exhibit complex cell diversities and organized architectures that resemble human brain development ranging from neural tube formation, neuroepithelium differentiation, neurogenesis and gliogenesis, to neural circuit formation. Rapid advancements in brain organoid culture technologies have allowed researchers to generate more accurate models of human brain development and neurological diseases. These models also allow for direct investigation of pathological processes associated with infectious diseases affecting the nervous system. In this review, we first briefly summarize recent advancements in brain organoid methodologies and neurodevelopmental processes that can be effectively modeled by brain organoids. We then focus on applications of brain organoids to investigate the pathogenesis of neurotropic viral infection. Finally, we discuss limitations of the current brain organoid methodologies as well as applications of other organ specific organoids in the infectious disease research.